2023
DOI: 10.1186/s12967-023-03986-y
|View full text |Cite
|
Sign up to set email alerts
|

FLI1 regulates radiotherapy resistance in nasopharyngeal carcinoma through TIE1-mediated PI3K/AKT signaling pathway

Abstract: Background Radiotherapy resistance is the main cause of treatment failure in nasopharyngeal carcinoma (NPC), which leads to poor prognosis. It is urgent to elucidate the molecular mechanisms underlying radiotherapy resistance. Methods RNA-seq analysis was applied to five paired progressive disease (PD) and complete response (CR) NPC tissues. Loss-and gain-of-function assays were used for oncogenic function of FLI1 both in vitro and in vivo. RNA-seq… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 66 publications
0
0
0
Order By: Relevance
“…More and more literature has demonstrated aberrant expression of TIE1 in diverse tumor types, with several studies indicating its potential role in promoting carcinogenesis and tumor progression. For example, breast cancer, colorectal cancer, nasopharyngeal carcinoma, to name a few 8 , 12 , 30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More and more literature has demonstrated aberrant expression of TIE1 in diverse tumor types, with several studies indicating its potential role in promoting carcinogenesis and tumor progression. For example, breast cancer, colorectal cancer, nasopharyngeal carcinoma, to name a few 8 , 12 , 30 .…”
Section: Discussionmentioning
confidence: 99%
“…TIE1 (tyrosine kinase with immunoglobulin-like and EGF-like domains 1) is a tyrosine kinase receptor, originally found in an erythroleukemia cell line 7 , 8 . Previous research has shown that TIE1 is primarily expressed in endothelial cells and plays a crucial role in the formation of blood and lymphatic vessels 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Radiotherapy plays a vital role in treating nasopharyngeal carcinoma 4 . Despite technological advances, the prognosis of NPC patients after radiotherapy varies widely 39 , possibly related to the development of radioresistance 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Genetic, viral, and dietary factors are implicated in the tumorigenesis of NPC 2 . Intensity-modulated radiotherapy is currently the primary management for NPC because of the radiosensitivity and complicated anatomic construction 3 , 4 . Although clinical treatment strategies are continuously advanced, partial patients exhibit unusual radioresistance, resulting in failure in therapy 5 .…”
Section: Introductionmentioning
confidence: 99%